Research progress of NF-κB signaling pathway and thrombosis - Wang, Zilong; Fang, Chucun; Yao, Mengting; Wu, Dongwen; Chen, Maga; Guo, Tianting; Mo, Jianwen (Frontiers in Immunology, 2023)
Venous thromboembolism is a very common and costly health problem. Deep vein thrombosis (DVT) can cause permanent damage to the venous system and lead to swelling, ulceration, gangrene, and other symptoms of the affected limb. In addition, more than half of the embolus of pulmonary embolism comes from venous thrombosis, which is the serious cause of death, second only to ischemic heart disease and stroke patients. It can be seen that deep vein thrombosis has become a serious disease affecting human health. In recent years, with the deepening of research, the inflammatory response is considered to be an important pathway to trigger the venous thromboembolism， in which the transcription factor NF-κB is the central medium of inflammation, and the NF-κB signaling pathway can regulate the pro-inflammatory and coagulation response, so to explore the mechanism and make use of it may provide new solutions for the prevention and treatment of thrombosis.